Kellogg on marketing - Tybout, Alice M.; Calder, Bobby J.; J.L. Kellogg Graduate School of Management (Hoboken, N.J. : Wiley, 2010)
The business classic, fully revised and updated for today's marketers. The second edition of Kellogg on Marketing provides a unique and highly regarded perspective on both the basics of marketing and on new issues that are challenging businesses today.: Includes more than 60% new material on both fundamental marketing concepts and hot topics such as Product Innovation, Social Media, Marketing to Consumers at the Bottom of the Pyramid, and Internal Branding; With a foreword by Philip Kotler; The Kellogg School of Management is recognized around the world as the leading MBA program in Marketing.
Kellogg on Marketing, Second Edition; Contents; Foreword: Thinking about Marketing; Preface; Section One: Developing a Marketing Strategy; Section Two: Implementing the Strategy; Section Section Three: Perspectives on Contemporary Issues in Marketing; Index.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Marketing; Marketing; Marketing; marketing; BUSINESS & ECONOMICS -- Distribution; BUSINESS & ECONOMICS -- Marketing -- General; Marketing